1990
DOI: 10.1159/000310128
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescein Angiography in Ciliary Body Melanomas

Abstract: We retrospectively studied the value of iris fluorescein angiography in predicitng benignity or malignancy in 10 cases of ciliary body melanoma with iris extension. No correlation between fluorescein-angiographic appearance and histopathologic features was observed. Fluorescein angiography adds little to the management of ciliary body melanomas with iris extension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1991
1991
1996
1996

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…In our case, re sults of the fluorescein angiographic study revealed a pat tern commonly observed in melanomas of the ciliary body [11][12][13],…”
Section: Discussionsupporting
confidence: 55%
“…In our case, re sults of the fluorescein angiographic study revealed a pat tern commonly observed in melanomas of the ciliary body [11][12][13],…”
Section: Discussionsupporting
confidence: 55%